The Impact of Digital Safety Competence on Cognitive Competence, AI Self-Efficacy, and Character - Cecilia M. S. Ma; Daniel T. L. Shek; Irene Y. H. Fan; Xixian Zhu; Xiangen Hu (Applied Sciences)
Although there are studies on digital competence in higher education, there are very few studies on digital safety competence. This study aims to explore the impact of digital safety competence on students’ higher-order thinking and AI-related outcomes. Using a cross-sectional design, 159 university students completed an online questionnaire to measure cognitive competence, Al self-efficacy, AI ethics, and moral competence. Results showed that digital safety competence was positively and significantly related to cognitive competence, AI self-efficacy, AI ethics, and moral competence (p < 0.05). Our study extends the literature by highlighting the role of digital safety competence. Educators and university policy makers may consider incorporating digital competence, especially in the area of safety, into their teaching and learning strategies.